Where are the Galapagos Islands? - Stine, Megan (Where are ---?, 2017)
"This book teaches readers about the Galapagos Islands, a chain of volcanic islands located on either side of the equator in the Pacific Ocean, and the strange and unique animals that live there. Some animals include the marine iguana, the blue-footed booby, the magnificent frigatebird and the giant Galapagos tortoise, which may live to be over one hundred years old. The islands, which were studies by Charles Darwin, are a popular tourist destination and a UNESCO World Heritage site"--